A quality approach on pile installation method / Faried Mohd Noor - Mohd Noor, Faried (Faculty of Civil Engineering, 2007)
In Malaysia, the application of the pile is very broaden. However, there is a limited study on the quality requirement of the piling industry. Quality requirement of pile installation method are very important in order to provide a safety of the structure in future and to provide the effectiveness performance of the pile. Toward the problem, this research will study on the type specifications of pile based on the type of the installation method such as driven piles, bored piles and jack-in piles. Further the study, the pile testing procedures also has been studied. Interviewing, site observation study, questionnaires and observation was selected as the methodologies method for this study. The site study will be planned to the site construction that involved with piling installation and pile testing performance in order to see the real work in construction industry. A set of questionnaire was distributed among the professional team such as contractor and consultant team. The results of the questionnaire and site observation have been identified in order to see the compliance activities based on the JKR specification. From the observation, the results of compliance are driven pile 87.41 %, maintained load test 97.64 % and pile driving analyzer 90.91 %. From the questionnaire, the results of compliance are driven pile 94.41 %, bored pile 63.63 %, jack-in pile 73.33 %, maintained load test 100.00 % and pile driving analyzer 52.74 %.